2019
DOI: 10.1111/anu.12930
|View full text |Cite
|
Sign up to set email alerts
|

Two filamentous microalgae as feed ingredients improved flesh quality and enhanced antioxidant capacity and immunity of the gibel carp (Carassius auratus gibelio)

Abstract: A 40‐day experiment was conducted to investigate the effects of two filamentous microalgae as feed ingredients on growth performance, tissue fatty acid profiles, pigmentation and immunity of gibel carp (204.83 ± 2.17 g, mean ± SD). Three diets (control, Oedocladium sp. and Tribonema sp.) were formulated. In the control diet, no microalgal meal was added and into the Oedocladium and Tribonema diets were added 40 g/kg Oedocladium sp. meal and 50 g/kg Tribonema sp. meal, respectively. Compared to the control, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…utriculosum meal increased the ratio of n‐3 to n‐6 PUFAs in fillet. Chen et al, (2019) also found that dietary supplementation of Tribonema meal increased the ratio of n‐3 to n‐6 PUFAs in gibel carp ( Carassius auratus gibelio ). These results demonstrate that T .…”
Section: Discussionmentioning
confidence: 96%
“…utriculosum meal increased the ratio of n‐3 to n‐6 PUFAs in fillet. Chen et al, (2019) also found that dietary supplementation of Tribonema meal increased the ratio of n‐3 to n‐6 PUFAs in gibel carp ( Carassius auratus gibelio ). These results demonstrate that T .…”
Section: Discussionmentioning
confidence: 96%
“…Similar results have been observed in kuruma prawn ( Marsupenaeus japonicus ) fed with the diet containing H. pluvialis (Chien & Shiau, 2005), Chinese horseshoe crabs ( Tachypleus tridentatus ) fed with the diet containing Spirulina platensis (Kwan, Chan, Cheung, & Shin, 2017), black tiger prawn ( Penaeus monodon ) fed with the diet containing Chlorella vulgaris (Li, Xiao, Mangott, Kent, & Pirozzi, 2016), and gibel carp fed with the diet containing 4% Oedocladium sp. or 5% T. utriculosum meal (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The source and biochemical composition of the microalgae used in this study were described in an earlier work of Chen et al (2019). Briefly, the Oedocladium sp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations